The End of the Cold War : European Unity, Socialism, and the Shift in Global Power - Denitch, Bogdan Denis (Book collections on Project MUSE., 1990)
The End of the Cold War was first published in 1990. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Against the backdrop of unprecedented change in the world political and social order, Bogdan Denitch charts the unique opportunities and potential pitfalls that accompany the increased economic and political integration of the European Community. Historically, any move toward unification has had broad ramifications. This, coming as it does in the wake of.